Cesium Carbonate Mediated Borylation of Aryl Iodides with Diboron in Methanol. Issue 28 (22nd August 2013) - Zhang, Jieming; Wu, Hai‐Hong; Zhang, Junliang
Abstract: Herein we describe the unexpected borylation of aryl iodides promoted by a Cs2 CO3 and MeOH system. This formal nucleophilic boryl substitution could be applied to a wide range of functionalized aryl iodide compounds. The preliminary results indicate that this process is neither copper catalyzed nor radical mediated. Abstract : Transition‐metal free! The unexpected borylation of aryl iodides promoted by Cs2 CO3 and MeOH is revealed. This formal nucleophilic boryl substitution can be applied to a wide range of functionalized aryl iodide compounds. The preliminary results indicate that this process is neither copper catalyzed nor radical mediated (pin = pinacolato, OCMe2 CMe2 O; neop = neopentylglycolato, OCH2 CMe2 CH2 O).